Efficacy of Albendazole Against Soil-transmitted Helminthiasis among Children in Asia: Systematic Review - M. Mohd Faizal; B. P. Anaanthan; M. Nur Ezdiani; M. N. Azmawati; A. Norfazilah; F. G. Hasanain; Mohammad Saffree Jeffree; Syed Sharizman Syed Abdul Rahim; Mohd Rohaizat Hassan (2020)
BACKGROUND: TheWorld health organization reported that 875 million children worldwide require antihelminth preventive chemotherapy annually. Vast majority of STH infections (67%) and YLDs (68%) occurred in Asia.METHODS: A systematic search was performed for relevant titles, abstract, and keywords from Cochrane Library, PubMed, and Scopus around October 2018 based on the PICO strategy. Out of 173 papers that were evaluated, final assessment for eligibility had yielded a total of five papers to be included for analysis covering period from 2013 to 2018.RESULTS: Of the five selected studies, three were randomized controlled trial, one was cohort and another one was described more like a quasi-experimental trial. All infection intensity showed improvement post-intervention. Four of the five studies used Kato Katz as diagnostic method with one combined it with Baermann techniques. One used McMaster egg counting method. All except one study tested albendazole efficacy in their study either alone or in combination with other chemotherapy such as diethyl carbazide or combining with education pamphlet. Egg reduction rate was reported as low as 63% and as high as 99.9%.